Are apprenticeships business cycle proof? - Samuel Lüthi; Stefan C. Wolter (Swiss Journal of Economics and Statistics, 2020)
Although there is evidence that apprenticeship training can ease the transition of youth into the labour market and thereby alleviate youth unemployment, many policymakers fear that firms will reduce the number of apprenticeship positions during economic crises, thus exacerbating the problem of youth unemployment. Using recent panel data of Swiss cantons and dynamic regression models, we examine the relationship between newly created apprenticeships and the business cycle. The empirical results suggest that economic shocks induce a pro-cyclical, moderate response in the apprenticeship market, both immediately and in subsequent years.
Keywords: 330; Apprenticeship training; VET; Education; Business cycle; Error correction model